(untitled) (Indian Journal of Public Health Research & Development, 2020)
Pregnancy is a period from conception to birth. During this period several physical and emotional changes occurs in women. Women should be physically and more over mentally prepared to have a baby in her womb. Miscarriage is spontaneous loss of the fetus before 20 weeks of gestation. The rate of miscarriage increases with a maternal age of less than 18years or an age of 35 years or more, an increasing number of previous miscarriage, and increasing parity. In rural population women are forced to marry at an early age. Objective: To study the quality of life on SF-36 questionnaire of women having adverse pregnancy outcomes. Materials and Methodology: The study was conducted in krishna institute of medical sciences ‘deemed to be’ university Karad. Subjects were selected according to inclusion and exclusion criteria. The subjects underwent test using quality of life questionnaire- SF36. Conclusion: The present study provided evidence to support the decline in quality of life of women with adverse pregnancy outcome.